2019
DOI: 10.1029/2018jd029033
|View full text |Cite
|
Sign up to set email alerts
|

Search for Microphysical Signatures of Stochastic Condensation in Marine Boundary Layer Clouds Using Airborne Digital Holography

Abstract: Droplet growth due to stochastic condensation has been considered as one of the mechanisms to cause broadening of cloud droplet size distributions and jump the bottleneck between droplet growth due to diffusion and collision‐coalescence. Digital in‐line holography is used to measure variations in droplet number concentration and droplet size in marine boundary layer clouds. Distributions of phase relaxation times are quite broad for some clouds. Turbulence correlation times are estimated, and the comparison of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 72 publications
(132 reference statements)
2
24
0
Order By: Relevance
“…Therefore, ψ can capture the main trend of the relationship between d and ψ, but does not well represent the fluctuation of d in each bin of ψ, which depends on stochastic processes. As discussed inDesai et al (2019), stochastic processes contribute significantly to the increase of d Tölle and Krueger (2014). also pointed out that droplets of different sizes experienced different supersaturation histories.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Therefore, ψ can capture the main trend of the relationship between d and ψ, but does not well represent the fluctuation of d in each bin of ψ, which depends on stochastic processes. As discussed inDesai et al (2019), stochastic processes contribute significantly to the increase of d Tölle and Krueger (2014). also pointed out that droplets of different sizes experienced different supersaturation histories.…”
mentioning
confidence: 91%
“…Furthermore, entrainment‐mixing processes have important effects on shaping cloud droplet size distributions (CDSDs) by affecting the local environments and trajectories of droplets (Cooper, 1989; Kumar et al, 2012). The relative width of CDSD is often represented by relative dispersion ( d ), defined as the ratio of standard deviation (σ) to mean radius of cloud droplets ( r m ), and its importance has been emphasized in the parameterizations of effective radius, autoconversion process (Beard & Ochs, 1993; Chandrakar et al, 2016; Cooper et al, 2013; Desai et al, 2019; Liu et al, 2002; Lu et al, 2020; Wang et al, 2011; Xie et al, 2013; Zhao et al, 2006, 2019), and cloud water sedimentation flux (Ackerman et al, 2009). Numerical simulations (Andrejczuk et al, 2004; Jensen & Baker, 1989; Lasher‐trapp et al, 2005; Su et al, 1998; Tölle & Krueger, 2014) and observations (Bera, Pandithurai, et al, 2016; Bera, Prabha, et al, 2016; Burnet & Brenguier, 2007; Haman et al, 2007; Jensen et al, 1985; Lu, Niu, et al, 2013) found that d and/or σ in diluted cloud was larger than that in near‐adiabatic cloud.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, diffusion growth theory has predicted a positive correlation between ε and cloud droplet number concentration ( N d ) (Liu & Daum, 2002; Yum & Hudson, 2005). While many studies (e.g., Desai et al., 2019; Liu et al., 2006; C. Lu et al., 2012; Pawlowska et al., 2006; J. Wang et al., 2009) have shown a negative correlation, some in situ measurements have shown neutral or unclear correlations between ε and N d (Zhao et al., 2006). Using three dimensional large‐eddy simulations of marine stratocumulus, M. L. Lu and Seinfeld (2006) found a decrease of ε with increasing aerosol number concentration due to the presence of smaller droplets associated with the higher aerosol concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, diffusion growth theory has predicted a positive correlation between ε and cloud droplet number concentration (N d ) (Liu & Daum, 2002;Yum & Hudson, 2005). While many studies (e.g., Desai et al, 2019;Liu et al, 2006;C. Lu et al, 2012;Pawlowska et al, 2006;J.…”
mentioning
confidence: 99%
“…For the cloud feature labelled B in Figure 3, we have a detection probability in the lin90 channel of about 6 × 10 −8 for the scattering from the cloud particles themselves; i.e., with aerosol background subtracted. It is reasonable to assume, on the basis of published cloud droplet size distributions [9,34], that the drop radii in the cloud are between 5 and 10 µm, and further that the droplets are not precipitating. In Figure 6, we highlight the contour of detection probability corresponding to the measured probability, for this range of radii.…”
mentioning
confidence: 99%